Marie Duval : maverick Victorian cartoonist - Grennan, Simon; Sabin, Roger, 1961-; Waite, Julian (Manchester University Press, 2020)
Marie Duval: maverick Victorian cartoonist offers the first critical appraisal of the work of Marie Duval 1847-1890), one of the most unusual, pioneering and visionary cartoonists of the later nineteenth century, focusing on new types of cultural work by women and establishing Duval as a unique but exemplary figure in a transformational period of the nineteenth century.
Keywords: De Tessier, Isabelle Émilie, -- 1847-1890 -- Criticism and interpretation.; Caricatures and cartoons -- Great Britain -- History -- 19th century.; Electronic books.; Caricatures et dessins humoristiques -- Grande-Bretagne -- Histoire -- 19e siècle.; Livres numériques.; e-books.; LITERARY CRITICISM / General.; Caricatures and cartoons; Great Britain; 1800-1899; History; Criticism, interpretation, etc.